(untitled) (Children’s Medicine of the North-West, 2021)
Acne (acne) is a chronic recurrent disease of the sebaceous glands and hair follicles. Acne is one of the most pressing problems of modern dermatology. This is due to the prevalence of this pathology, an increase in the number of intractable forms, as well as an increase in resistance to antibacterial drugs. The first manifestation is more often manifested during puberty, affects up to 85 % of boys and girls aged 12 to 24 years, and 10 % persists until the age of 25–45 years.